Nationalist Discourses from Thai Historical Films in the Ayutthaya Period (2000 -2018 A.D) - Chartsiri, Jirathorn (Opción)
The purpose of this research was to analyze the nationalist discourses from Thai historical films from 2000 – 2018. The finding indicated that most of Thai historical films in the Ayutthaya period from 2000 -2018 were focused on the concept of nationalism and patriotism which are products of modernity that occurred after Thailand turned into the modern nation-state. These Thai films were used as an instrument to motivate nationalism and cultivate patriotism in audiences by created the common enemy which is Burmese who overpowered Ayutthaya twice in her long history.